TIPE KESALAHAN MAHASISWA DALAM MENYELESAIKAN SOAL-SOAL GEOMETRI BERDASAR NEWMANâS ERROR ANALYSIS (NEA) - Utami, Anita Dewi (IKIP PGRI Madiun, 2016)
The students ability to solve mathematical problems are affected directly or indirectly by their pattern of problem solving when they were attending primary and secondary schools. The result of observation shows that there are students who can not answer proving problem and take no action at all, thoughit is only at the step of understanding the problem. NEA is a frame work with simple diagnostic procedures, which include (1) decoding, (2) comprehension, (3) transformation, (4) process skills, and (5) encoding. Newmanâs developed diagnostic method is used to identify the error categories of descriptive test answer. Therefore, the descriptive types of studentsâ error in proving problem solving in Geometry 1 subject based on Newmanâs error Analysis (NEA), and what are the causes for the studentâs mistakes in solving those proving problem, especially in Geometry1 subject is interesting to be discussed in this article.Â Kemampuan mahasiswa dalam menyelesaikan soal-soal matematika secara langsung ataupun tidak langsung dipengaruhi oleh pola penyelesaian soal pada saat mahasiswa duduk di bangku sekolah dasar maupun menengah. Hasil pengamatan peneliti menujukkan bahwa masih terdapat mahasiswa yang tidak bisa menjawab soal pembuktian dan tidak melakukan tindakan apapun, meskipun hanya pada tahapanunderstand the problem. NEA merupakan kerangka kerja dengan prosedur diagnostik sederhana, yang meliputi (1) decoding, (2) comprehension, (3)transformation, (4) processskill, dan (5) encoding. Metode diagnostik yang dikembangkan Newman ini digunakan untuk mengidentifikasi kategori kesalahan terhadap jawaban dari sebuah tes uraian. Sehingga bagaimana deskripsi jenis kesalahan mahasiswa dalam menyelesaikan soal-soal pembuktian pada mata kuliah Geometri 1 berdasarkan Newmanâs Error Analysis(NEA), dan apa saja penyebab kesalahan mahasiswa dalam menyelesaikan soal-soal pembuktian, khususnya pada mata kuliah Geometri 1, menarik untuk dibahas dalam tulisan ini.Â